Psychometric Properties of a Generic, Patient-Centred Palliative Care Outcome Measure of Symptom Burden for People with Progressive Long Term Neurological Conditions. - Wei Gao; Vincent Crosby; Andrew Wilcock; Rachael Burman; Eli Silber; Nilay Hepgul; K Ray Chaudhuri; Irene J Higginson; OPTCARE Neuro trial (PLoS ONE)
Background There is no standard palliative care outcome measure for people with progressive long term neurological conditions (LTNC). This study aims to determine the psychometric properties of a new 8-item palliative care outcome scale of symptom burden (IPOS Neuro-S8) in this population. Data and methods Data were merged from a Phase II palliative care intervention study in multiple sclerosis (MS) and a longitudinal observational study in idiopathic Parkinson's disease (IPD), multiple system atrophy (MSA) and progressive supranuclear palsy (PSP). The IPOS Neuro-S8 was assessed for its data quality, score distribution, ceiling and floor effects, reliability, factor structure, convergent and discriminant validity, concurrent validity with generic (Palliative care Outcome Scale) and condition specific measures (Multiple Sclerosis Impact Scale; Non-motor Symptoms Questionnaire; Parkinson's Disease Questionnaire), responsiveness and minimally clinically important difference. Results Of the 134 participants, MS patients had a mean Extended Disability Status Scale score 7.8 (SD = 1.0), patients with an IPD, MSA or PSP were in Hoehn & Yahr stage 3-5. The IPOS Neuro-S8 had high data quality (2% missing), mean score 8 (SD = 5; range 0-32), no ceiling effects, borderline floor effects, good internal consistency (Cronbach's α = 0.7) and moderate test-retest reliability (intraclass coefficient = 0.6). The results supported a moderately correlated two-factor structure (Pearson's r = 0.5). It was moderately correlated with generic and condition specific measures (Pearson's r: 0.5-0.6). There was some evidence for discriminant validity in IPD, MSA and PSP (p = 0.020), and for good responsiveness and longitudinal construct validity. Conclusions IPOS Neuro-S8 shows acceptable to promising psychometric properties in common forms of progressive LTNCs. Future work needs to confirm these findings with larger samples and its usefulness in wider disease groups.